STATISTICAL DATA ANALYSIS OF GAMMA-RAY BACKGROUND SPECTRA FOR QUALITY ASSURANCE PURPOSES - Wasim, M.; Arif, M. (The Nucleus, 2010)
Twenty five gamma-ray spectra were accumulated in the gamma-ray spectrometry laboratory located at the Chemistry Division, PINSTECH, Islamabad over a period of three years. Different background components along with their variation with time have been discussed in this paper. It was found that natural component of the background radiations can be reduced with a better design of shielding around the detector. However, the component from the fission products cannot be reduced by increased shielding but with a better shielding material containing less or no fission products.